Articulation Disorder in Reversed Occlusion Patients Needing Surgical Orthodontic Treatment - YAMAMOTO, Yuko (THE JAPANESE JOURNAL OF COMMUNICATION DISORDERS, 1993)
To study articulation disorders in reversed occlusion patients we administered speech tests for 211 patients expecting surgical orthodontic treatment. We investigated 195 patients excluding 16 patients with lip and tongue defects. The results indicated that the degree of intelligibility of speech in 193 out of 195 patients (99%) was within the normal range. Slight misarticulations, if they occurred, hardly affected speech. Articulatory errors were observed in 146 out of 195 patients (74.9%), nearly 60% of which were interdental articulation. Most of them occurred in fricative and affricative dental and alveolar consonants. Lateralized articulation, 9.4% of articulation disorders, which was small in ratio, but lateralized articulation severely affected the speech sound.